Vegetation diversity of Pinus pinaster forests in the Italian Peninsula - Dario Ciaramella; Martina Marei Viti; Marco Landi; Kryštof Chytrý; Claudia Angiolini; Gianmaria Bonari (Vegetation Classification and Survey (VCS))
Aim: To revise Pinus pinaster-dominated communities of the Italian peninsula with special regard to central-southern Tuscany, and assess their floristic and ecological differences. Study area: Tuscany and Liguria regions, Italy. Methods: We classified 251 vegetation plots using the Two-way indicator species analysis method and we explored vegetation patterns through Principal Coordinate Analysis. We then investigated the ecology using Ecological Indicator Values. Results: We identified four major groups, primarily distinguished by the substrate of their stands and along a latitudinal gradient. We classified the forests in central-southern Tuscany in the association Erico scopariae-Pinetum pinastri. This community includes thermophilous and mesophilous species primarily distributed in the Atlantic and Western Mediterranean regions. Comparison of community means of Ecological Indicator Values revealed significant differences in soil reaction, nitrogen, moisture, and light conditions, but not in temperature, between the central-southern Tuscany forests and the other clusters. We classified the other studied forest communities on acidic substrates within the association Erico arboreae-Pinetum pinastri, whereas those found on ultramafic substrates were placed in the Euphorbio ligusticae-Pinetum pinastri typus cons. propos., and in an informal group of secondary vegetation stands. Conclusions: Our analyses showed that the Pinus pinaster-dominated forests of central-southern Tuscany belong to the association Erico scopariae-Pinetum pinastri of the alliance Genisto pilosae-Pinion pinastri (class Pinetea halepensis). The presence of species of phytogeographical importance in the forest understory, underscores the high biogeographic and conservation value of these pine forests. Taxonomic reference: Euro+Med (2024-). Syntaxonomic reference: Mucina et al. (2016), except for the changes proposed by Bonari et al. (2021). Abbreviations: EVC = EuroVegChecklist; ICPN = International Code of Phytosociological Nomenclature; PCoA = Principal Coordinate Analysis; TWINSPAN = Two-way indicator species analysis.